First Results of the Intraformational Conglomerate Test of the Late Riphean Katav Formation (Southern Urals) - N. P. Parfiriev; K. N. Danukalov; I. V. Golovanova; S. A. Dyakova (Учёные записки Казанского университета: Серия Естественные науки)
Detailed petrographic, electron-microscopic, and paleomagnetic studies were conducted on flatbedded synsedimentary carbonate breccias from three blocks of rocks (one block from Minyar, two blocks from Katav-Ivanovsk) to verify the ideas about the time of formation of the high-temperature component (HTC) of natural remanent magnetization (Jn) of limestones from the Upper Riphean Katav Formation, Southern Urals. Petrographic and electron-microscopic observations revealed that the composition of pebbles corresponds to that of the host matrix rocks, thus enabling the use of an intraformational conglomerate test. In all the studied blocks, the distribution of paleomagnetic directions for pebbles is generally chaotic, with the concentration parameter not exceeding 3. These test results meet the Graham criterion. The pebbles’ average Jn have a larger confidence oval and differ significantly from the matrix’s directions with a much smaller confidence oval. The Hodges-Ajne test was applied to the blocks from Katav-Ivanovsk. The Rayleigh test was used for the block from Minyar. The results obtained at this stage indicate that the HTC of magnetization of the Katav limestones may have a primary origin. If this is confirmed, the Katav Formation would be a good paleomagnetic record of the Earth’s Neoproterozoic history and provide valuable insights into the geomagnetic field behavior in the Late Precambrian.